Análise da situação da inseminação artificial bovina no estado de Goiás - GORDO, João Maurício Lucas (2011)
This study aimed to diagnose the situation and use of artificial insemination (AI) and fixed-time artificial insemination in Goiás State, Brazil. A literature review was carried out and economic costs related to herd conception in natural mating systems, AI and TAI were calculated. Subsequently, an approach to cattle farmer´s profile, farm characterization and speech analysis was fulfilled in order to better understand biodemographic characteristics and to obtain cattle breeder´s discourse concerning AI technology. Using semi-structured questionnaires 71 interviews were accomplished to dairy and beef cattle farmers from different municipalities of Goiás State during AI training courses in 2010 and 2011. The interviews pointed out that 92% were male farmers and 29.6% had 31 to 41 years old. Schooling stage varied and 34% declared to have finished the last grade, 15.5% had primary grade complete and 14% had yet not finished primary education. 46.5% had between 9 and 20 years of cattle production experience, 25.5% more than 20 years and 28% had up to 8 years of experience. 53.5% already used AI or TAI before the training courses. Considering farmers that previously used any biotechnique, exclusive use of AI is more frequent (68,5%)than the association of both biotechniques (18.5%), and more frequent than the exclusive use of TAI (13%). 46.5% raised between 31 and 90 heifers and cows and 27% raised up to 30. Speech analysis revealed that personal motivation is a major topic involving the IA adoption process, which is related to the benefits of the biotechnique and the phenotype of the animals rather than economic factors. Prerequisites necessary for adoption is the second factor, mainly related to labor force, infrastructure and cattle handling, followed by social motivation topics, mainly associated to institutes and people related to IA and the everyday life of cattle farmers. Note: Thesis in four chapters with summary and abstract. Was cited only the summary / abstract of the first chapter